Critical Education in the New Information Age - Giroux, Henry A.; Flecha, Ramón; Freire, Paulo; Macedo, Donaldo; Castells, Manuel (Rowman & Littlefield Publishers, 1999)
Essays by some of the world's leading educators provide a revolutionary portrait of new ideas and developments in education that can influence the possibility of social and political change. The authors take into account such diverse terrain as feminism, ecology, media, and individual liberty in their pursuit of new ideas that can inform the fundamental practice of education and promote a more humane civil society. The book consolidates recent thinking just as it reflects on emerging new lines of critical theory.